Stress at ultimate in unbonded tendons for ungrouted post-tensioned masonry beams (2017)
Accurate estimation of tendon stress is crucial for calculating the flexural capacity of post-tensioned masonry members. Tendon stresses in bonded elements may be calculated based on strain-compatibility. For unbonded tendons, stresses depend on the relative displacement between the tendon's anchor points, and strain-compatibility is not totally applicable to calculate stresses. Masonry codes in some countries provide equations for unbonded, post-tensioned members that are based on modified strain-compatibility approaches for calculating stress increases in unbonded tendons at ultimate; some of these equations required calibration using statistical evaluation of experimental results and finite-element analysis. A new approach to calculate tendon stress increase, based on the theory of beam deformation, in the elastic zone, and a plastic hinge with a geometric curvature distribution in the inelastic region, is reported here for the calculation of the stress increase at ultimate. To compare the accuracy of code equations and that of the proposed methodology, a database of test results for post-tensioned, simply supported, flexure critical masonry beams has been used. This comparison shows that the proposed equation provides an accurate prediction of tendon stress at ultimate for post-tensioned masonry beams. © 2017 Elsevier Ltd